Reducing Flight Delays and Disruptions in Airline Operations - Kopchenova, Kseniia (2024)
This Bachelor's thesis examines the causes of flight delays and disruptions in airline operations and proposes practical solutions to enhance operational efficiency. Using Failure Mode and Effects Analysis (FMEA), the study systematically identifies key areas of concern and provides improvement proposals to mitigate these challenges. By analyzing various causes of flight delays, this research offers valuable insights into the factors affecting airline operations. The proposed improvement actions aim to reduce flight delays, improve on-time performance, and enhance customer satisfaction within the aviation industry.